Assessment of water quality using the Canadian index CWQI - Case study of the Orontes River in Hama Governorate – Syria - AlFattamah, Ammar Mahmoud; Sabbouh, Houssam Shafeek; Jafar, Raed Salman (Journal of engineering sciences and information technology, 2022)
The aim of the study is to address the issues and associated health risks due to consumption of high pollution parameters in parts of the Orontes River basin, Hama governorate, Syria using the Canadian Water Quality index (CWQI), as an appropriate tool in classifying and studying the impact of spatial and seasonal changes on pollution loads.In this study, 9 parameters (pH, BOD5, NH4+, CL-, PO4-, Na+, Total Hardness, Turbidity, Conductivity) were taken from 9 stations along the river, One-Way ANOVA and Pearson correlation coefficient were applied separately for all parameters, and a value of ρ
Keywords: Water quality; seasonal changes; spatial changes; water pollution; Orontes River